IS OLATION OF PROBIOTIC CANDIDATE BACTERIA FROM GIANT GOURAMY (Osphronemus gouramy Lac.) INTESTINE TO CONTROL Aeromonas hydrophila - Lola Pitaloka br Barus; Iesje Lukistyowati; Nursyirwani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aimed to isolate and to find the bacteria that potential as probiotic candidate from Giant Gouramy (Osphronemus gouramy Lac.) intestine cultivated in Riau provincial to be used to control MAS (Motile Aeromonas Septicemia) desease. Survey method and experiment method were conducted in this study. Bacteria was isolated from the fish intestine, and was inoculated on TSA and MRS agar at different pH level (2,4, and 6). The isolateis were indentified by morphological observation, physiological and biochemical test, and by using API 50 CHL test kit. Antibacterial activity of the isolated against Aeromonas hydrophila was tested by the paper disk diffusion method. Eighteen isolates of probiotic candidates were found, and indicated optimal growth in all pH treatment. Based on morphological, physiological test, and biochemichals test, three genus of bacteria were identified as Bacillus sp., Lactobacillus sp., and Bifidobacterium sp. The highest antibacterial activity against A. hydrophila was indicated by Isolate G63 with inhibition zone of 13,2 mm. Based API 50 CHL test kit the isolate was categorized in to Lactobacillus planatarum at similarity level of 84%.Keywords: Giant Gouramy, intestine, isolate, probiotic candidate